STUDI FENOMENOLOGI: PEMAKNAAN TERHADAP PENGALAMAN KEKERASAN DALAM BERPACARAN (DATING VIOLENCE) PADA REMAJA AKHIR DI KOTA KUPANG - Filomena Since; Christiani Natasya Miru; Diana Aipipidely; M.K.P. Abdi Keraf (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Dating violence is an increasingly concerning phenomenon among late adolescents, particularly in Kupang City. This study aims to gain an in-depth understanding of the meaning-making of dating violence experiences among late adolescents in Kupang City, as well as to describe the meaning-making process experienced by victims, encompassing the aspects of meaning discrepancy, searching for meaning, cognitive reappraisal, finding meaning, and psychological adjustment based on Park's meaning-making theory. This study employed a qualitative research design with a descriptive phenomenological approach. Participants consisted of five late adolescents aged 18–22 years who had experienced dating violence in Kupang City, selected through purposive sampling and snowball sampling techniques. Data were collected through semi-structured interviews. Data analysis followed Colaizzi's phenomenological analysis procedure through seven stages. Data validity was established through member checking and audit trail. The results revealed six main themes: the ideal relationship concept, experiences of violence, responses and perceptions toward violence, the process of searching for and transforming meaning, meaning-making of the violence experience, and post-violence adjustment. All participants experienced more than one form of violence, including verbal and emotional violence, psychological violence, physical violence, sexual violence, and excessive control and monitoring. Participants initially tended to deny the violence, justify their partner's behavior, and engage in self-blame. Over time, with social support from those closest to them, participants began to recognize themselves as victims, found meaning in their experiences, and achieved more adaptive adjustment. The violence experience was ultimately interpreted as a valuable lesson regarding self-worth, relational boundaries, and personal growth. ABSTRAK Dating violence merupakan fenomena mengkhawatirkan pada remaja akhir di Kota Kupang yang membutuhkan pemahaman kualitatif mendalam. Penelitian fenomenologi deskriptif ini bertujuan menggambarkan proses pemaknaan pengalaman kekerasan berpacaran berdasarkan teori meaning-making Park mencakup ketidaksesuaian makna hingga penyesuaian psikologis. Subjek terdiri atas lima remaja akhir berusia 18–22 tahun korban kekerasan yang dipilih melalui purposive dan snowball sampling. Pengumpulan data menggunakan wawancara semi-terstruktur yang dianalisis melalui tujuh tahapan kualitatif Colaizzi dengan member check. Hasil penelitian mengungkap enam tema utama: gambaran hubungan ideal, pengalaman kekerasan, respons emosional, pencarian makna, pemaknaan baru, dan penyesuaian pasca-kejadian. Partisipan mengalami kekerasan verbal, fisik, psikologis, dan kontrol berlebihan yang awalnya direspons dengan penyangkalan serta self-blame. Seiring berjalannya waktu dan hadirnya dukungan sosial, terjadi pergeseran kognitif menuju kesadaran diri sebagai penyintas. Pengalaman traumatis dimaknai sebagai pelajaran berharga mengenai penguatan harga diri, penetapan batasan hubungan, dan pendewasaan pribadi. Kesimpulannya, analisis meaning-making terbukti efektif memfasilitasi transformasi kognitif dan penyesuaian psikologis adaptif bagi korban kekerasan dalam berpacaran.